2021
DOI: 10.1212/wnl.0000000000011702
|View full text |Cite
|
Sign up to set email alerts
|

Association of White Matter Hyperintensities With HIV Status and Vascular Risk Factors

Abstract: Objective:To test the hypothesis that brain white matter hyperintensities (WMH) are more common in people living with HIV (PLWH), even in the setting of well-controlled infection, and to identify clinical parameters that correlate with these abnormalities.Methods:Research brain MRI scans, acquired within longitudinal studies evaluating neurocognitive outcomes, were reviewed to determine WMH load using the Fazekas visual rating scale in PLWH with well-controlled infection (antiretroviral therapy for at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…Our study population shows that CSVD is more prevalent in subjects with HIV compared to controls (79% HIV+ vs. 63% HIV–) in an older population as determined by higher rates and volumes of WMHs, consistent with other studies ( Mina et al, 2021 , Moulignier et al, 2018 ). This increased prevalence of WMHs is likely driven by chronic HIV inflammation affecting the microcirculation and vascular inflammation associated with systemic vascular risk factors ( Lopez-Candales et al, 2017 , Mina et al, 2021 , Willerson and Ridker, 2004 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study population shows that CSVD is more prevalent in subjects with HIV compared to controls (79% HIV+ vs. 63% HIV–) in an older population as determined by higher rates and volumes of WMHs, consistent with other studies ( Mina et al, 2021 , Moulignier et al, 2018 ). This increased prevalence of WMHs is likely driven by chronic HIV inflammation affecting the microcirculation and vascular inflammation associated with systemic vascular risk factors ( Lopez-Candales et al, 2017 , Mina et al, 2021 , Willerson and Ridker, 2004 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to measuring WMHs as in previous studies ( Mina et al, 2021 , Moulignier et al, 2018 ), our study also used QSM to further investigate microstructural iron concentration. We found significant positive correlations between the Reynolds cardiovascular risk score and QSM in the subcortical DGM and across the entire brain in both the HIV+ and HIV– populations ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although WMHs are imaging biomarkers of covert cerebrovascular disease frequently studied among PLWH and associated with aging and longer duration of HIV infection, 26 sex differences have been underexplored in this populatoion. 1 This pilot study expands on the existing literature by investigating the role of reproductive hormones and other risk factors as predictors of white matter disease as a function of sex within the context of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that people with HIV are at higher risk of an increased burden of WMH compared to uninfected controls. 142,143 Several limitations of our study must be acknowledged. First, many of our EWAS discoveries were not independently confirmed.…”
Section: Discussionmentioning
confidence: 96%